The transcript repeat element: The human Alu sequence as a component of gene networks influencing cancer - Moolhuijzen, Paula; Kulski, J.; Dunn, D.; Schibeci, D.; Barrero, R.; Gojobori, T.; Bellgard, M. (2010)
A small percentage (3%) of the 1.3 million copies of Alu sequences in the human genome is expressed individually or as part of various gene transcripts with potential regulatory and pathophysiological importance. In order to better understand the role of repetitive elements within transcripts, this review focuses on Alu-containing transcripts of normal and cancerous tissue in a transcriptome-wide survey of the H-Invitational human transcript database on 106,825 tissue-derived transcripts expressed at 29,979 loci. The Alu elements in transcripts of cancerous tissues are significantly underrepresented in comparison to those in normal tissues. In this review, we propose a model for Alu-mediated siRNA down-regulation of Alu-containing transcripts in cancer tissues. In cancer or other rapidly dividing tissues, hypomethylation of repeat element regions triggers the expression of transposon elements including Alu, which can potentially form double-stranded RNA molecules for use as templates to generate Alu-derived siRNAs (Alu-siRNAs). The generated Alu-siRNAs target endogenous messenger RNAs harbouring sequence similarity to Alu elements. This model correlates with the observation that there is substantial under-representation of Alu-containing mRNAs in cancer cells. This new perspective of gene regulation in disease conditions can provide a basis for starting to account for changes in complex gene network in cancer. © 2010 Springer-Verlag.